Pemisahan Hidrokarbon dalam Limbah Katalis Asam (Spent Acid) Proses Alkilasi Olefin dan Isoparafin dengan Proses Presipitasi - Elda Melwita; Syukron Habibie; Abdul Apandi (CHEMICA: Jurnal Teknik Kimia, 2019)
Alkylation of olefin and isoparaffin produces spent acid waste containing high concentration of hydrocarbon. The content of sulphuric acid and hydrocarbon in spent acid put this waste into hazardous waste classification, therefore must be treated to avoid environmental pollution. Hydrocarbon separation can be carried out using precipitation. Two precipitation methods were applied to precipitate hydrocarbon, namely neutralization, and antisolvent precipitation. Neutralization was conducted using NaOH, CaCO3, and CaO. Meanwhile, antisolvent precipitation was performed using water. Precipitation of hydrocarbon using CaCO3 and CaO showed very satisfying results. On the other hand, NaOH was failed to precipitate hydrocarbon. Hydrocarbon was also precipitated using water as antisolvent at ratio of spent acid:water (g/ml) of 200.